Correlating the size and cation inversion factor in context of magnetic and optical behavior of CoFe2O4 nanoparticles. Issue 36 (3rd June 2020) - Singh, Jitendra Pal; Park, Jae Yeon; Singh, Varsha; Kim, So Hee; Lim, Weon Cheol; Kumar, Hemaunt; Kim, Y. H.; Lee, Sangsul; Chae, Keun Hwa
Abstract : Herein, the size dependent behavior of cobalt ferrite nanoparticles was investigated using synchrotron radiation based techniques. Abstract : Herein, the size dependent behavior of cobalt ferrite nanoparticles was investigated using synchrotron radiation based techniques. Scanning electron micrographs revealed the enhancement of particle/crystallite size with increase of annealing temperature. Moreover, the shape of these particles also changed with increase of crystallite size. Saturation magnetization increased with increase of crystallite size. The higher saturation magnetization for larger crystallite size nanoparticles was attributed to a cation distribution similar to that of bulk CoFe2 O4 . The optical band-gap of these nanoparticles decreased from 1.9 eV to 1.7 eV with increase of crystallite size. The enhancement of the optical band-gap for smaller crystallites was due to phenomena of optical confinement occurring in the nanoparticles. Fe L Co L-edge near edge extended X-ray absorption fine structure (NEXAFS) measurements showed that Fe and Co ions remain in the 3+ and 2+ state in these nanoparticles. The results obtained from Fe & Co K-edge X-ray absorption near edge structure (XANES)-imaging experiments further revealed that this oxidation state was possessed by even the crystallites. Extended X-ray absorption fine structure (EXAFS) measurements revealed distribution of Fe and Co ions among tetrahedral (A) and octahedral (B) sites of the spinel structure which corroborates the results obtained from Rietveld refinement of X-ray diffraction patterns (XRD). X-ray magnetic circular di-chroism (XMCD) measurements revealed negative exchange interaction among the ions situated in tetrahedral (A) and octahedral (B) sites. Theoretical and experimental calculated magnetic moments revealed the dominancy of size effects rather than the cation redistribution in the spinel lattice of CoFe2 O4 nanoparticles.